VІІ INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE «UKRAINE, BULGARIA, EU: MODERN TRENDS IN THE DEVELOPMENT OF SCIENCE, TECHNOLOGY AND INNOVATION»: Ukraine, Bulgaria, EU: modern trends in the development of science, technology and innovation: materials VІІ International Scientific and Practical Conference (Burgas, Bulgaria, July 2-7, 2023) Burgas: Avangard Prima, 2023. 134 p. (2024)
The collection of conference materials included the reports that became the subject of discussion by the participants of the VІІ International Scientific and Practical Conference “Ukraine, Bulgaria, EU: modern trends in the development of science, technology and innovation”, held in Burgas (Bulgaria) on July 2-7, 2023 at the University “Prof. Dr. Arsen Zlatarov”.Conference materials may be of interest to researchers, teachers, researchers, students of higher educational institutions.